The Influence of Eco-Friendly Packaging, Emotional Branding, and Digital Customer Experience on Brand Preference of Health Products - Anastasia d'Ornay; Muhammad Zakaria; Apriani Riyanti; Fahrina Mustafa; Ayu Ratna Wulandari; Josef Hernawan Nudu (Journal of Innovative and Creativity, 2025)
The core goal of the research is to determine the impact of green packaging, emotional branding, and digital customer experience on the selection of health products' brands. The main reasons for this study are the demand for green products, emotional connection with brands, and the migration of consumers from offline to online for information and purchases. The research employed a quantitative explanatory design with health product consumers being the sample population of 200 participants, who had online interaction with the brands and were selected through purposive sampling. The instrument of the study was initially evaluated for validity and reliability and then underwent classical assumption tests prior to the application of multiple linear regression analysis. Each of the three independent variables was found to have a major beneficial impact on brand preference. The coefficient of determination value shows that the model is capable of explaining the variations in brand preference. This study, when considering its theoretical implications, adds to the existing understanding of the topic of consumer behavior and modern marketing strategies in the health care sector. Additionally, the findings of the study provide a roadmap for companies to gain competitive advantage by incorporating eco-friendly packaging, upgrading emotional branding, and digitalizing experiences to facilitate brand preference creation more effectively.